Transforming Cognitive and Emotional Dissonance for Physiotherapy Students Learning Medical Anthropology - H. Macdonald (South African Journal of Physiotherapy, 2013)
Since the 1980s physiotherapy has shifted concerns towardscultural, economic, philosophical, political and social questions, and moreflexible ways of speaking about and practicing physiotherapy. In response to bothglobal shifts and local demands, the Physiotherapy Division at the University ofCape Town (UC T) approached their Social Anthropology colleagues to teacha broader range of perspectives to their physiotherapy students. The objectiveof this research was to explore the changes experienced by UC T physiotherapystudents exposed to a cross-disciplinary teaching environment, and discuss thepossible role of the course in affecting their experience. A qualitative researchdesign drew data from multiple sources and was analysed using an interpretivecontent analysis method. Using an anthropological model of transformation,the changes experienced by students were categorised into three sub-categories of ‘separation’, ‘transition’ and ‘incorporation’.Emotional and cognitive changes were attributable to the course material. By attending to their emotional discomfort, physiotherapystudents not only successfully incorporated anthropological concepts to healthcare but also improved their professional identitiesand personal self-worth.